Sampling, nonresponse, and weighting of the 2020 refreshment sample (M6) of the IAB-BAMF-SOEP refugee panel - Hans Walter Steinhauer; Rainer Siegers; Manuel Siegert; Jannes Jacobsen; Sabine Zinn (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
This paper provides details on the sampling design, fieldwork, nonresponse, and population adjustments for the 2020 sample M6 of the Socio-Economic Panel (SOEP). Sample M6 refreshes the SOEP core samples M3, M4, and M5, sampling households of refugees who arrived in Germany between January 2013 and the end of December 2016. The sample also augments the SOEP core by sampling households of refugees who arrived in Germany between January 2017 and June 2019. Obtaining nearly 1,000 household interviews and panel consent of households for each sample was complicated by the first wave of the Covid-19 pandemic and the first lockdown. Nevertheless, nonresponse on the household level is driven by a variety of characteristics, such as nationality or regional contexts as well as interviewer characteristics.
Keywords: 330